(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Structures consisting of Flat slabs posses’ great advantage over conventional structures with usual slab beam design. Because of the freedom to design space, shorter construction time, architectural functional as well as economical elements, flat slab building structures have significant benefits. Flat slab structural systems are substantially more flexible than standard RC frame systems due to the lack of deep beams and shear walls, making them more vulnerable during seismic occurrences. The slab column connections, i.e., the shear force in the slab at the connection, should always keep its bearing capacity even at maximum displacements, is altogether a vital moment in the design of these systems. Building construction has a significant impact on the behaviour of flat slab buildings during earthquakes. As a result of this fact, it is necessary to take due consideration and to discover how to assure the safety of tall structures against earthquake forces.